PENGARUH PENGENDALIAN INTERN DAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA BPR DENGAN MANAJEMEN RESIKO SEBAGAI VARIABEL MODERASI - Rangga Sudana, I Putu Ekapratama; Dwirandra, A.A.N. Bagus; Astika, Ida Bagus Putra; Ratna Sari, Maria Mediatrix (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.08.TAHUN.2022, 2022)
This research studies the influence of internal and good corporate governance on the performance of Rural Banks (BPR) with risk management as a moderating variable with a study on BPR in Badung Regency. The purpose of this study was to determine the effect of internal control and good corporate governance on BPR performance and to determine the effect of risk management as a moderating variable between internal control and good corporate governance on BPR performance. This research is explanatory research that tries to test the hypothesis statistically and explain it descriptively and quantitatively. The research data was collected through a survey with the distribution of questionnaires as a research instrument. The research population is the leaders of BPRs throughout Badung Regency. The number of samples in the study were 49 BPR leaders. The research instrument in the form of a questionnaire was used to collect data in the form of opinions related to internal control, good corporate governance, risk management and performance of rural banks throughout Badung Regency. The results showed that the internal control and good corporate governance simultaneously did not have a significant effect on the performance of BPR. In addition, the moderating variable, namely risk management, can weaken the relationship between internal control and good corporate governance on BPR performance.